Simulating Effects of Variable Stoichiometry and Temperature on Mixotrophy in the Harmful Dinoflagellate Karlodinium veneficum - Lin, Chih-Hsien; Flynn, Kevin J.; Mitra, Aditee; Glibert, Patricia M. (Frontiers in Marine Science, 2018)
A dynamic mathematical model is presented simulating the growth of the harmful algal bloom (HAB) mixotrophic dinoflagellate Karlodinium veneficum and its algal prey, Rhodomonas salina. This model describes carbon-nitrogen-phosphorus-based interactions within the mixotroph, interlinking autotrophic and phagotrophic nutrition. The model was tuned to experimental data from these species grown under autotrophic conditions and in mixed batch cultures in which nitrogen:phosphorus stoichiometry (molar N:P of 4, 16 and 32) of both predator and prey varied. With a single set of parameter values defining mixotroph and prey physiology, a good fit was attained to all experimentally-derived carbon biomass data. The potential effects of temperature and nutrients changes on promoting growth of prey and thus K. veneficum bloom formation were explored using this simulation platform. The modeled biomass of K. veneficum was highest when they consumed prey under high N:P conditions. The modeled scenarios under low N:P conditions responded differently, and showed larger deviation between mixotrophic and autotrophic growth, depending on temperature. When inorganic nutrients were in balanced proportions, lower biomass of the mixotroph was attained at all temperatures in the simulations, suggesting that natural systems might be more resilient against Karlodinium HAB development in warming temperatures if nutrients were available in balanced proportions. The models highlight the importance of consideration of particulate prey in modeling HAB dynamics. The simulations also imply that warmer, wetter springs that may bring more N, such as predicted under climate change for Chesapeake Bay, may be more conducive to development of these HABs. Prey availability may also increase with temperature due to differential growth temperature responses of K. veneficum and its common prey.